Sliding friction-induced surface reinforcement in AgCuNi–WS2–MoS2 composites: Exploring friction performance enhancements - Xiuchong Zhu; Youwang Tu; Lei Zhang; Yong He; Bo Luo; Xiao Kang; Yanmin Liu (Journal of Materials Research and Technology)
Silver matrix composites are widely used in conductive slip ring components due to their excellent electrical conductivity and low friction properties. However, long-term use can lead to a decrease in the mechanical properties and service life of the materials, so improving the mechanical strength and wear resistance of the brush materials is a goal that researchers have been pursuing. In this study, the surface of the composite material was strengthened by sliding friction treatment (SFT) technique, and then the surface mechanical properties and wear resistance of AgCuNi-MoS2-WS2 composites were analysed. The results showed that the SFT treatment formed a wear-resistant layer on the material surface. Nanoindentation measurements showed that the hardness of the 40 N treated group was significantly increased by 44.9% compared to the untreated group at a load of 50 mN. In addition, micron scratch tests showed that the average coefficient of friction of the composites was reduced by 16.5% from 0.236 to 0.197 at a load of 150 mN. These findings highlight the feasibility of SFT as a method to improve the micromechanical and friction and wear properties of these composites.